Осмислення Голодомору у світлі конвенції ООН про геноцид - Сербин, Р. (Архіви України, 2008)
The author conducts an analysis of the UN Convention on Genocide (1948), examining a possible interpretation of the 1932-1933 Famine in Ukraine as genocide on the basis of the noted document as well as its further implementation in international legal practices.